The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1115/1.2800825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperactivity of the Lateral Pterygoid Muscle on the Temporomandibular Joint Disk

Abstract: In this study, the effect of hyperactivity of the lateral pterygoid muscle (LPM) on the temporomandibular joint (TMJ) disk during prolonged clenching was examined with a mathematical model. Finite element models of the TMJ were constructed based on magnetic resonance images from two subjects with or without internal derangement of the TMJ. For each model, muscle forces were used as a loading condition for stress analysis for 10 min clenching. Furthermore, an intermittent increase of the LPM force with interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…The inferior head of the LPM is active during jaw opening, jaw protrusion, and contralateral jaw movements and the superior head of the LPM during jaw closing, jaw retrusion, and ipsilateral jaw movements. Both heads have a reciprocal pattern of activity; however, intermingling of muscle bundles between the different heads has been observed anatomically (Tanaka et al, 2007;Fujita et al, 2001). It attaches to the capsule and the pterygoid fovea of the mandibular condyle, and may also insert directly into the disc (Bertilsson and Strom 1995;Naidoo, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…The inferior head of the LPM is active during jaw opening, jaw protrusion, and contralateral jaw movements and the superior head of the LPM during jaw closing, jaw retrusion, and ipsilateral jaw movements. Both heads have a reciprocal pattern of activity; however, intermingling of muscle bundles between the different heads has been observed anatomically (Tanaka et al, 2007;Fujita et al, 2001). It attaches to the capsule and the pterygoid fovea of the mandibular condyle, and may also insert directly into the disc (Bertilsson and Strom 1995;Naidoo, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…Since the superior head of LPM attaches partly to the articular capsule of the TMJ and directly or indirectly to its articular disc [18,19], it has been hypothesized that dysfunction of this muscle can lead to degenerative changes [15,16]. Tanaka et al [20] recently investigated the effect of hyperactivity of LPM on the disc during prolonged clenching using a finite element (FE) model of the TMJ. The findings suggested that the hyperactivity of the LPM might be involved in the progression of abnormal anterior disc displacement.…”
Section: Introductionmentioning
confidence: 99%
“…To Tanaka et al (2007), LPM hyperactivity can cause progression of anterior disc displacement, while Taskaya-Yilmaz et al indicate that this disc condition causes morphological changes in the SHLP associated with lower muscular activity. The assumption that anterior disc displacement is caused by the overactivity of the SHLP has justified the development of therapies that aim to block the activity of the muscle fibers (Bakke et al, 2005); however, the existing literature offers insufficient evidence to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%